Community Relations Pt. Pertamina Pasca Meledaknya Depo Pertamina Plumpang - Abdur Rahman Al Akmal; Alief Givani Ramadhan; Zhilal Rahmansyah; Tria Patrianti (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2024)
This research aims to analyze the dynamics of the relationship between the community and PT. Pertamina following the explosion at the Pertamina Plumpang Depot. The study employs a qualitative approach, collecting data through observation, media monitoring, and company documents. The results indicate that the explosion event has significantly impacted the relationship between PT. Pertamina and the surrounding community. Concerns, uncertainty, and a sense of insecurity among the public have posed various challenges in maintaining a harmonious relationship. Despite PT. Pertamina's efforts to improve its image and address the negative impacts, there remains an expansion of perceptual gaps between the company and the community. The implications of these findings can serve as a foundation for PT. Pertamina and relevant stakeholders in designing more effective communication strategies to strengthen post-incident community relations.